Geomeasure: GIS and Scripting for Measuring Morphometric Variability. (3rd July 2019) - Cortell-Nicolau, Alfredo
ABSTRACT: This paper presents Geomeasure, a methodological tool developed to recover typometric information with a twofold objective. First, to speed up the process of gathering data by automatizing the way in which it is recovered. Second, it adds higher accuracy and the possibility of re-measuring archeological items without further directly interacting with the piece. Based on a combination of R scripting with GIS features, Geomeasure is at the time able to automatically gather 125–130 typometric variables per archaeological item, with the only input of vectorized photographs. It can be used as a reliable methodological aid to extract detailed information on patterns and trends of shape variability. The system has currently been applied over a sample of 2, 000+ geometric microliths in the Eastern Iberian Peninsula. The performance results of its application are on display, and the system is compared to other methodological approaches currently in use for capturing shape variability.